Self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances as well as preparation method and application of self-reinforced absorbable composite material

Through the self-reinforced composite material of polyester fiber/calcium phosphate substances, combined with fiber annealing and stretching processes, the problem of insufficient mechanical properties of polyester fiber reinforced polyester matrix is ​​solved, and efficient manufacturing and safe degradation of bone joint materials are achieved. Significantly improves fracture healing efficiency.

CN119185667APending Publication Date: 2024-12-27CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411362376.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The mechanical properties of existing polyester fiber reinforced polyester matrix have not yet met the requirements for improvement, and are inefficient in processing, are not suitable for manufacturing complex shapes and small devices, and degradation in the human body may cause sterile inflammation.

Method used

Using self-reinforced absorbable composite materials of polyester fiber/calcium phosphate substances, bone screws with significant improvement in mechanical properties and controllable degradation rate are prepared through blending injection molding or solid extrusion processes, combined with fiber annealing and stretching. and bone junction plates, and introduce elements such as zinc, strontium, magnesium into the material to alleviate inflammation and promote bone tissue healing.

Benefits of technology

It significantly improves the mechanical properties of bone screws and bone plates, shortens the time for bone tissue regeneration, reduces sterile inflammation, improves processing efficiency, and achieves product batch stability and small individual differences.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005065263790000011
    Figure HDA0005065263790000011
  • Figure HDA0005065263790000012
    Figure HDA0005065263790000012
  • Figure HDA0005065263790000021
    Figure HDA0005065263790000021
Patent Text Reader

Abstract

The invention provides a self-reinforced absorbable composite material containing a polyester fiber / calcium phosphate substance. The absorbable bone screw and the absorbable bone plate prepared from the polyester fiber self-reinforced absorbable composite material provided by the invention have the advantages that the mechanical property is obviously improved, the degradation rate is controllable, the bone tissue regeneration induction time is shortened, the aseptic inflammation is relieved, the individual difference is small, and the processing efficiency is obviously improved. According to the absorbable composite material prepared by the invention, the polyester fibers and the polyester matrixes are various, and the mechanical property and the degradation rate of the composite material can be regulated and controlled through matching and combination of the fibers and the matrixes, so that the clinical requirements of fixing different fracture injuries are met; moreover, high-activity calcium phosphate substances doped with specific elements such as zinc, strontium and magnesium are further adopted, so that the aseptic inflammation caused by acidic degradation substances can be relieved, and higher osteogenic activity, higher angiogenesis promoting capability and the like are realized, so that injured bone tissues are induced to be healed more quickly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyester material medical implant devices, and relates to a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances, and a preparation method and application thereof. Background Art

[0002] Bone fractures and cracks caused by traffic accidents, falls, sports injuries, external impacts, etc. often require the implantation of bone screws and bone plates for internal fixation of the injured area. Although metal bone screws and bone plates have high strength, they cannot be absorbed by the human body and require secondary surgery to remove, which increases the patient's physical and mental pain and medical expenses; and the strength of metal bone screws and bone plates is often much higher than that of human bones, resulting in a stress shielding effect, causing the side effect of osteoporosis in patients. Absorbable polyester materials represented by polylactic acid have good biocompatibility and can be absorbed and metabolized by the human body. Making them into bone screws and bone plates can solve the problem of secondary removal. In addition, by establishing appropriate reinforcement, toughening modification strategies and formula compositions, the mechanical properties and degradation rate of absorbable polyester composites can be effectively regulated to form a good match with the mechanical properties requirements of the rehabilitation process of the fracture site.

[0003] Therefore, many corresponding studies are currently focused on polyester composite materials. Among the many modification methods, the method of using polyester fiber to reinforce the polyester matrix has unique advantages, but its mechanical properties still need to be improved. At the same time, polyester fiber reinforced polyester matrix generally adopts hot pressing molding method for polyester fiber self-reinforcement: polyester fiber braids are prepared by weaving and winding, and then the braids and polyester sheets are prepared into composite materials by hot pressing molding. However, this type of method has shortcomings: ① The processing efficiency is low and it is not suitable for continuous and large-scale preparation; ② The fibers are distributed layer by layer in the matrix, and the reinforcement effect is not uniform; ③ It is not suitable for manufacturing devices with complex shapes and small sizes. Moreover, during the metabolism of polyester materials in the human body, small molecules of hydroxy acids will be degraded, causing aseptic inflammation around the implantation site.

[0004] Therefore, how to find a more suitable way to solve the above-mentioned problems existing in existing polyester self-reinforced absorbable composite materials is also one of the urgent problems to be solved by many front-line researchers and R&D-based production companies in the industry. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances and its preparation method and application. The polyester fiber self-reinforced absorbable composite material provided by the present invention has significantly improved mechanical properties of absorbable bone screws and absorbable bone plates, controllable degradation rate, shortened induction of bone tissue regeneration time, reduced aseptic inflammation, and stable product batches with small individual differences, while significantly improving processing efficiency.

[0006] The present invention provides a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate material, comprising: an absorbable polyester material matrix and polyester fiber and calcium phosphate material composited in the absorbable polyester material matrix;

[0007] The absorbable polyester material matrix includes one or more of a L-polylactic acid matrix, a copolymer matrix of L-lactide and D-lactide, a copolymer matrix of glycolide and lactide, and a copolymer matrix of lactide and trimethylene carbonate;

[0008] The polyester fiber includes one or more of stereocomposite polylactic acid fiber, highly oriented polylactic acid fiber, poly(lactide-glycolide) fiber and poly(glycolide) fiber;

[0009] The calcium phosphate material includes one or more of calcium phosphate substances, polyester grafted calcium phosphate substances, and calcium phosphate substances doped with functional elements.

[0010] Preferably, the calcium phosphate substance includes hydroxyapatite and / or tricalcium phosphate;

[0011] The polyester monomer in the polyester graft-modified calcium phosphate substance includes one or more of glycolide, lactide and caprolactone monomers;

[0012] The functional elements include one or more of zinc, strontium and magnesium;

[0013] In the self-reinforced absorbable composite material, the mass fraction of the polyester fiber is 1% to 50%;

[0014] In the self-reinforced absorbable composite material, the mass fraction of the absorbable polyester material matrix is ​​50% to 99%;

[0015] In the self-reinforced absorbable composite material, the mass fraction of calcium phosphate substances is 1% to 30%.

[0016] Preferably, the stretching ratio of the highly oriented polylactic acid fiber is 110% to 400%;

[0017] The topological structure of the L-polylactic acid matrix includes a linear structure and a multi-arm structure;

[0018] The number average molecular weight of the linear structured L-polylactic acid is 80,000 to 200,000 Da;

[0019] The number average molecular weight of the multi-arm structured L-polylactic acid is 5,000 to 30,000 Da.

[0020] Preferably, the stereocomposite polylactic acid fiber is prepared from left-handed polylactic acid and right-handed polylactic acid or prepared from a block copolymer of left-handed lactide and right-handed lactide;

[0021] The number average molecular weight of the L-polylactic acid is 50,000 to 200,000 Da;

[0022] The number average molecular weight of the dextrorotatory polylactic acid is 50,000 to 200,000 Da;

[0023] The number average molecular weight of the block copolymer of L-lactide and D-lactide is 50,000 to 200,000 Da;

[0024] The self-reinforced absorbable composite material is a material for implanting medical devices.

[0025] The present invention also provides a method for preparing a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate material as described in any one of the above technical solutions, comprising the following steps:

[0026] The polyester fiber, the calcium phosphate material and the absorbable polyester material matrix are mixed by injection molding or solid extrusion to obtain a self-reinforced absorbable composite material;

[0027] The stereocomposite polylactic acid fiber is obtained by co-extrusion of left-handed polylactic acid and right-handed polylactic acid, melt spinning, fiber annealing and fiber stretching; or by room temperature blending of left-handed polylactic acid and right-handed polylactic acid, melt spinning, fiber annealing and fiber stretching; or by melt spinning, fiber stretching and fiber annealing of a block copolymer of left-handed lactide and right-handed lactide;

[0028] The highly oriented polylactic acid fiber is obtained by melt spinning, fiber stretching and fiber annealing of left-handed polylactic acid or right-handed polylactic acid;

[0029] The poly(glycolide-lactide) fiber is obtained by melt spinning, fiber annealing and fiber stretching of glycolide-lactide copolymer;

[0030] The polyglycolide fiber is obtained by melt spinning, fiber annealing and fiber stretching of polyglycolide.

[0031] Preferably, the polyester grafted calcium phosphate substance is obtained by grafting one or more of glycolide monomers, lactide monomers and caprolactone monomers onto the surface of calcium phosphate substances or calcium phosphate substances doped with functional elements through chemical reaction, and then initiating ring-opening polymerization of the monomers;

[0032] In the chemical reaction, the molar ratio of one or more of the glycolide monomer, the lactide monomer and the caprolactone monomer to the calcium phosphate substance or the calcium phosphate substance doped with the functional element is (1:3) to (3:1);

[0033] In the process of preparing stereocomposite polylactic acid fiber from L-polylactic acid and D-polylactic acid, the processing temperature of the co-extrusion is 220-240°C; the processing temperature of the melt spinning is 220-240°C; the temperature of the fiber annealing is 80-210°C; the multiple of the fiber stretching is 110%-400%; the temperature of the fiber stretching is 80-210°C; the mass ratio of the L-polylactic acid to the D-polylactic acid is (1:3)-(3:1);

[0034] In the process of preparing stereocomposite polylactic acid fiber from the block copolymer of left-handed lactide and right-handed lactide, the processing temperature of the melt spinning is 150-240°C; the temperature of the fiber annealing is 80-210°C; the fiber stretching multiple is 110%-400%; the fiber stretching temperature is 80-210°C; the molar ratio of left-handed lactide to right-handed lactide in the block copolymer of left-handed lactide and right-handed lactide is (2:3)-(3:2).

[0035] Preferably, in the process of preparing highly oriented polylactic acid fibers from the left-handed polylactic acid or the right-handed polylactic acid, the processing temperature of the melt spinning is 150-200°C; the temperature of the fiber annealing is 70-200°C; the fiber stretching multiple is 110%-400%, and the fiber stretching temperature is 70-200°C; the number average molecular weight of the left-handed polylactic acid or the right-handed polylactic acid is independently selected from 50,000 to 200,000 Da;

[0036] In the process of preparing poly(glycolide-lactide) fiber from the glycolide-lactide copolymer, the processing temperature of the melt spinning is 150-250° C.; the temperature of the fiber annealing is 70-230° C.; the fiber stretching multiple is 110%-400%, and the fiber stretching temperature is 70-230° C.; the number average molecular weight of the glycolide-lactide copolymer is 50,000-200,000 Da;

[0037] In the process of preparing polyglycolide from polyglycolide, the processing temperature of melt spinning is 200-250°C; the temperature of fiber annealing is 70-230°C; the fiber stretching multiple is 110%-400%, and the fiber stretching temperature is 70-230°C; the number average molecular weight of polyglycolide is 50,000-200,000 Da;

[0038] The processing temperature of the solid state extrusion is 80 to 240°C;

[0039] The processing temperature of the blending injection molding is 150-240°C.

[0040] The present invention also provides a self-reinforced absorbable composite material profile containing polyester fiber / calcium phosphate substances, wherein the self-reinforced absorbable composite material profile containing polyester fiber / calcium phosphate substances is obtained by extruding and / or stretching a self-reinforced absorbable composite material blank containing polyester fiber / calcium phosphate substances;

[0041] The self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances includes the self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances described in any one of the above technical solutions or the self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances prepared by the preparation method described in any one of the above technical solutions.

[0042] Preferably, the extrusion temperature is 80-200°C;

[0043] The extrusion multiple is specifically, profile length / parison length is (1.2-5):1;

[0044] The stretching temperature is 80 to 200° C.

[0045] The stretching multiple is specifically, profile length / parison length is (1.2-5):1;

[0046] The self-reinforced absorbable composite material profile is specifically a self-reinforced absorbable composite material profile with oriented reinforcement.

[0047] The present invention also provides the self-reinforced absorbable composite material profile described in any one of the above technical solutions, the self-reinforced absorbable composite material profile prepared by the preparation method described in any one of the above technical solutions, or the use of the self-reinforced absorbable composite material profile described in any one of the above technical solutions in the preparation of implantable medical devices.

[0048] The present invention provides a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate, comprising: an absorbable polyester material matrix and polyester fibers and calcium phosphate materials composited in the absorbable polyester material matrix; the absorbable polyester material matrix comprises one or more of a left-handed polylactic acid matrix, a copolymer matrix of left-handed lactide and right-handed lactide, a copolymer matrix of glycolide and lactide, and a copolymer matrix of lactide and trimethylene carbonate; the polyester fiber comprises one or more of a stereocomposite polylactic acid fiber, a highly oriented polylactic acid fiber, polyglycolide-lactide fiber, and polyglycolide fiber; the calcium phosphate material comprises one or more of calcium phosphate substances, polyester graft-modified calcium phosphate substances, and calcium phosphate substances doped with functional elements. Compared with the prior art, the polyester fiber self-reinforced absorbable composite material provided by the present invention has significantly improved mechanical properties of absorbable bone screws and absorbable bone plates, controllable degradation rate, shortened induction of bone tissue regeneration time, reduced aseptic inflammation, and stable product batches, small individual differences, and significantly improved processing efficiency. The absorbable composite material prepared by the present invention has various types of polyester fibers and polyester matrices, and the mechanical properties and degradation rate of the composite material can be regulated by matching and combining the fibers and the matrix, thereby meeting the clinical needs of fixing different fracture injuries; and the absorbable composite material prepared further adopts highly active calcium phosphate substances doped with specific elements such as zinc, strontium, and magnesium, which can not only reduce aseptic inflammation caused by acidic degradation substances, but also has stronger osteogenic activity, angiogenesis-promoting ability, etc., thereby inducing faster healing of damaged bone tissue.

[0049] The experimental results show that the mechanical properties of the absorbable bone screws and bone plates prepared by the self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances provided by the present invention are significantly improved, among which the bending strength of the bone screw can reach 460MPa, the bending modulus can reach 8.1GPa, and the impact strength can reach 360kJ / m 2 , tensile strength can reach 210MPa, tensile modulus can reach 5.1GPa, torsional yield strength can reach 110MPa. The bending strength of the bone plate can reach 160MPa, the bending modulus can reach 4.1GPa, and the impact strength can reach 35kJ / m 2 , the tensile strength can reach 110MPa, and the tensile modulus can reach 3.1GPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 The hydrogen nuclear magnetic resonance spectrum of the L-polylactic acid synthesized in Example 2 of the present invention;

[0051] Figure 2 The differential scanning calorimetry curve of the dextrorotatory polylactic acid synthesized in Example 2 of the present invention;

[0052] Figure 3 Scanning electron microscope photograph of sc-PLA fibers prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0053] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0054] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0055] There is no particular restriction on the purity of all raw materials in the present invention. The present invention preferably uses analytically pure materials or materials with conventional purity requirements in the field of preparation of self-reinforced absorbable composite materials.

[0056] The brands and abbreviations of all raw materials of the present invention are conventional brands and abbreviations in the art. Each brand and abbreviation is clear and definite in the field of its related use. Those skilled in the art can purchase them from the market or prepare them by conventional methods according to the brands, abbreviations and corresponding uses.

[0057] The present invention provides a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate material, comprising: an absorbable polyester material matrix and polyester fiber and calcium phosphate material composited in the absorbable polyester material matrix;

[0058] The absorbable polyester material matrix includes one or more of a left-handed polylactic acid matrix, a copolymer matrix of left-handed lactide and right-handed lactide, a copolymer matrix of glycolide and lactide, and a copolymer matrix of lactide and trimethylene carbonate. It can be a left-handed polylactic acid matrix, a copolymer matrix of left-handed lactide and right-handed lactide, a copolymer matrix of glycolide and lactide, or a copolymer matrix of lactide and trimethylene carbonate.

[0059] The polyester fiber includes one or more of stereocomposite polylactic acid fiber, highly oriented polylactic acid fiber, poly(lactide-glycolide) fiber and poly(glycolide) fiber, and can be stereocomposite polylactic acid fiber, highly oriented polylactic acid fiber, poly(lactide-glycolide) fiber or poly(glycolide) fiber.

[0060] The calcium phosphate material includes one or more of calcium phosphate substances, polyester-grafted calcium phosphate substances, and calcium phosphate substances doped with functional elements. It can be calcium phosphate substances, polyester-grafted calcium phosphate substances, or calcium phosphate substances doped with functional elements.

[0061] In the present invention, the calcium phosphate substance preferably includes hydroxyapatite and / or tricalcium phosphate, and more preferably hydroxyapatite or tricalcium phosphate.

[0062] In the present invention, the polyester monomer in the polyester-grafted calcium phosphate material preferably includes one or more of glycolide, lactide and caprolactone monomers, and more preferably glycolide, lactide or caprolactone monomers.

[0063] In the present invention, the functional element preferably includes one or more of zinc, strontium and magnesium, and more preferably zinc, strontium or magnesium.

[0064] In the present invention, in the self-reinforced absorbable composite material, the mass fraction of the polyester fiber is preferably 1% to 50%, more preferably 10% to 40%, and more preferably 20% to 30%.

[0065] In the present invention, in the self-reinforced absorbable composite material, the mass fraction of the absorbable polyester material matrix is ​​preferably 50% to 99%, more preferably 60% to 90%, and more preferably 70% to 80%.

[0066] In the present invention, in the self-reinforced absorbable composite material, the mass fraction of calcium phosphate substances is preferably 1% to 30%, more preferably 5% to 25%, and more preferably 10% to 20%.

[0067] In the present invention, the stretching ratio of the highly oriented polylactic acid fiber is preferably 110% to 400%, more preferably 150% to 350%, and more preferably 200% to 300%.

[0068] In the present invention, the topological structure of the L-polylactic acid matrix preferably includes a linear structure and a multi-arm structure.

[0069] In the present invention, the number average molecular weight of the linear poly(L-lactic acid) is preferably 80,000 to 200,000 Da, more preferably 100,000 to 180,000 Da, and even more preferably 120,000 to 160,000 Da.

[0070] In the present invention, the number average molecular weight of the multi-arm structured L-polylactic acid is preferably 5,000 to 30,000 Da, more preferably 10,000 to 25,000 Da, and even more preferably 15,000 to 20,000 Da.

[0071] In the present invention, the stereocomposite polylactic acid fiber is preferably prepared from left-handed polylactic acid and right-handed polylactic acid or prepared from a block copolymer of left-handed lactide and right-handed lactide.

[0072] In the present invention, the number average molecular weight of the L-polylactic acid is preferably 50,000 to 200,000 Da, more preferably 80,000 to 170,000 Da, and even more preferably 110,000 to 140,000 Da.

[0073] In the present invention, the number average molecular weight of the dextrorotatory polylactic acid is preferably 50,000 to 200,000 Da, more preferably 80,000 to 170,000 Da, and even more preferably 110,000 to 140,000 Da.

[0074] In the present invention, the number average molecular weight of the block copolymer of L-lactide and D-lactide is preferably 50,000 to 200,000 Da, more preferably 80,000 to 170,000 Da, and even more preferably 110,000 to 140,000 Da.

[0075] Copolymer matrix of L-lactide and D-lactide, copolymer matrix of glycolide and lactide, and copolymer matrix of lactide and trimethylene carbonate

[0076] In the present invention, the number average molecular weight of the copolymer matrix of L-lactide and D-lactide is preferably 80,000 to 200,000 Da, more preferably 100,000 to 170,000 Da, and even more preferably 120,000 to 150,000 Da.

[0077] In the present invention, in the copolymer matrix of L-lactide and D-lactide, the molar ratio of L-lactide to D-lactide is preferably (85:15) to (99:1), more preferably (87:18) to (97:3), and more preferably (90:10) to (95:5).

[0078] In the present invention, the number average molecular weight of the copolymer matrix of glycolide and lactide is 80,000 to 200,000 Da, more preferably 100,000 to 170,000 Da, and more preferably 120,000 to 150,000 Da.

[0079] In the present invention, in the copolymer matrix of glycolide and lactide, the molar ratio of glycolide to lactide is preferably (1:99) to (99:1), more preferably (20:80) to (80:20), and more preferably (40:60) to (60:40).

[0080] In the present invention, the number average molecular weight of the copolymer matrix of lactide and trimethylene carbonate is 80,000 to 200,000 Da, more preferably 100,000 to 170,000 Da, and even more preferably 120,000 to 150,000 Da.

[0081] In the present invention, in the copolymer matrix of lactide and trimethylene carbonate, the molar ratio of lactide to trimethylene carbonate is (85:15) to (99:1), more preferably (87:18) to (97:3), and more preferably (90:10) to (95:5).

[0082] In the present invention, the self-reinforced absorbable composite material is preferably a material for implanting medical devices.

[0083] The present invention provides a method for preparing a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate material as described in any one of the above technical solutions, comprising the following steps:

[0084] The polyester fiber, the calcium phosphate material and the absorbable polyester material matrix are mixed by injection molding or solid extrusion to obtain a self-reinforced absorbable composite material;

[0085] The stereocomposite polylactic acid fiber is obtained by co-extrusion, melt spinning, fiber annealing and fiber stretching of left-handed polylactic acid and right-handed polylactic acid; or by room temperature (5-40° C.) blending (if blended at room temperature, the co-extrusion step is not required), melt spinning, fiber annealing and fiber stretching of left-handed polylactic acid and right-handed polylactic acid; or by melt spinning, fiber stretching and fiber annealing of a block copolymer of left-handed lactide and right-handed lactide;

[0086] The highly oriented polylactic acid fiber is obtained by melt spinning, fiber stretching and fiber annealing of left-handed polylactic acid or right-handed polylactic acid;

[0087] The poly(glycolide-lactide) fiber is obtained by melt spinning, fiber annealing and fiber stretching of glycolide-lactide copolymer;

[0088] The polyglycolide fiber is obtained by melt spinning, fiber annealing and fiber stretching of polyglycolide.

[0089] In the present invention, the polyester grafted modified calcium phosphate substance is preferably obtained by grafting one or more of glycolide monomers, lactide monomers and caprolactone monomers onto the surface of calcium phosphate substances or calcium phosphate substances doped with functional elements through chemical reaction, and then initiating monomer ring-opening polymerization.

[0090] In the present invention, in the chemical reaction, the molar ratio of one or more of the glycolide monomer, the lactide monomer and the caprolactone monomer to the calcium phosphate substance or the calcium phosphate substance doped with a functional element is preferably (1:3) to (3:1), more preferably (1.4:2.6) to (2.6:1.4), and more preferably (1.8:2.2) to (2.2:1.8).

[0091] In the present invention, in the process of preparing stereocomposite polylactic acid fiber from left-handed polylactic acid and right-handed polylactic acid, preferably, the processing temperature of the co-extrusion is 220-240°C; the processing temperature of the melt spinning is 220-240°C; the temperature of the fiber annealing is 80-210°C; the multiple of the fiber stretching is 110%-400%; the temperature of the fiber stretching is 80-210°C. More preferably, the processing temperature of the co-extrusion is 224-236°C; the processing temperature of the melt spinning is 224-236°C; the temperature of the fiber annealing is 100-190°C; the multiple of the fiber stretching is 150%-350%; the temperature of the fiber stretching is 100-190°C. More preferably, the processing temperature of the co-extrusion is 228-232°C; the processing temperature of the melt spinning is 228-236°C; the temperature of the fiber annealing is 120-170°C; the multiple of the fiber stretching is 200%-300%; the temperature of the fiber stretching is 120-170°C. The mass ratio of the L-polylactic acid to the D-polylactic acid is preferably (1:3)-(3:1), more preferably (1.4:2.6)-(2.6:1.4), and more preferably (1.8:2.2)-(2.2:1.8).

[0092] In the present invention, in the process of preparing stereocomposite polylactic acid fiber from the block copolymer of left-handed lactide and right-handed lactide, the processing temperature of the melt spinning is preferably 150-240°C; the temperature of the fiber annealing is 80-210°C; the fiber stretching multiple is 110%-400%; the fiber stretching temperature is 80-210°C; more preferably, the processing temperature of the melt spinning is 170-220°C; the fiber annealing temperature is 100-190°C; the fiber stretching multiple is 150%-350%; the fiber stretching temperature is 100-190°C; more preferably, the processing temperature of the melt spinning is 190-200°C; the fiber annealing temperature is 120-170°C; the fiber stretching multiple is 200%-300%; the fiber stretching temperature is 120-170°C. The molar ratio of L-lactide to D-lactide in the block copolymer of L-lactide and D-lactide is preferably (2:3) to (3:2), more preferably (2.2:2.8) to (2.8:2.2), and more preferably (2.4:2.6) to (2.6:2.4).

[0093] In the present invention, in the process of preparing highly oriented polylactic acid fiber from the left-handed polylactic acid or the right-handed polylactic acid, the processing temperature of the melt spinning is preferably 150-200°C; the temperature of the fiber annealing is 70-200°C; the fiber stretching multiple is 110%-400%, and the fiber stretching temperature is 70-200°C; more preferably, the processing temperature of the melt spinning is 160-190°C; the fiber annealing temperature is 90-180°C; the fiber stretching multiple is 150%-350%, and the fiber stretching temperature is 90-180°C; more preferably, the processing temperature of the melt spinning is 170-180°C; the fiber annealing temperature is 110-160°C; the fiber stretching multiple is 200%-300%, and the fiber stretching temperature is 110-160°C. The number average molecular weight of the L-polylactic acid or the D-polylactic acid is preferably independently selected from 50,000 to 200,000 Da, more preferably 80,000 to 170,000 Da, and even more preferably 110,000 to 140,000 Da.

[0094] In the present invention, in the process of preparing poly(lactide-glycolide) fiber from the glycolide-lactide copolymer, preferably the processing temperature of the melt spinning is 150-250°C; the temperature of the fiber annealing is 70-230°C; the fiber stretching multiple is 110%-400%, and the fiber stretching temperature is 70-230°C; more preferably, the processing temperature of the melt spinning is 170-230°C; the fiber annealing temperature is 100-200°C; the fiber stretching multiple is 150%-350%, and the fiber stretching temperature is 100-200°C; more preferably, the processing temperature of the melt spinning is 190-210°C; the fiber annealing temperature is 130-170°C; the fiber stretching multiple is 200%-300%, and the fiber stretching temperature is 130-170°C. The number average molecular weight of the glycolide-lactide copolymer is preferably 50,000 to 200,000 Da, more preferably 80,000 to 170,000 Da, and even more preferably 110,000 to 140,000 Da.

[0095] In the present invention, in the process of preparing polyglycolide fiber from polyglycolide, preferably the processing temperature of melt spinning is 200-250°C; the temperature of fiber annealing is 70-230°C; the fiber stretching multiple is 110%-400%, and the fiber stretching temperature is 70-230°C; more preferably, the processing temperature of melt spinning is 210-240°C; the temperature of fiber annealing is 100-200°C; the fiber stretching multiple is 150%-350%, and the fiber stretching temperature is 100-200°C; more preferably, the processing temperature of melt spinning is 220-230°C; the temperature of fiber annealing is 130-170°C; the fiber stretching multiple is 200%-300%, and the fiber stretching temperature is 130-170°C. The number average molecular weight of the polyglycolide is preferably 50,000-200,000 Da, more preferably 80,000-170,000 Da, and more preferably 110,000-140,000 Da.

[0096] In the present invention, the processing temperature of the solid-state extrusion is preferably 80 to 240°C, more preferably 110 to 210°C, and more preferably 140 to 170°C.

[0097] In the present invention, the processing temperature of the blending injection molding is preferably 150-240°C, more preferably 170-220°C, and more preferably 190-200°C.

[0098] The invention also provides a left-handed polylactic acid matrix and a stereocomposite polylactic acid fiber, and corresponding preparation methods.

[0099] In the present invention, the topological structure of the L-polylactic acid matrix includes a linear structure and a multi-arm structure.

[0100] In the present invention, the L-polylactic acid matrix is ​​specifically L-polylactic acid with a linear topological structure and L-polylactic acid with a multi-arm topological structure.

[0101] In the present invention, the multi-arm structure preferably includes one or more of three arms, four arms, six arms and eight arms, and more preferably three arms, four arms, six arms or eight arms.

[0102] In the present invention, the stereocomplex polylactic acid fiber is preferably a polylactic acid fiber containing stereocomplex crystals.

[0103] In the present invention, the number average molecular weight of the linear poly(L-lactic acid) is preferably 80,000 to 200,000 Da, more preferably 100,000 to 180,000 Da, and even more preferably 120,000 to 160,000 Da.

[0104] In the present invention, the number average molecular weight of the multi-arm structured L-polylactic acid is preferably 5,000 to 30,000 Da, more preferably 10,000 to 25,000 Da, and even more preferably 15,000 to 20,000 Da.

[0105] In the present invention, in the stereocomposite polylactic acid fiber, the mass ratio of L-polylactic acid to D-polylactic acid is preferably (1:3) to (3:1), more preferably (1.4:2.6) to (2.6:1.4), and more preferably (1.8:2.2) to (2.2:1.8). Specifically, the molar ratio of L-polylactic acid to D-polylactic acid in the present invention is 1:1.

[0106] In the present invention, the number average molecular weight of the L-polylactic acid is preferably 50,000 to 200,000 Da, more preferably 80,000 to 170,000 Da, and even more preferably 110,000 to 140,000 Da.

[0107] In the present invention, the number average molecular weight of the dextrorotatory polylactic acid is preferably 50,000 to 200,000 Da, more preferably 80,000 to 170,000 Da, and even more preferably 110,000 to 140,000 Da.

[0108] In the present invention, the preparation process preferably includes extrusion, melt spinning, fiber annealing and fiber drawing.

[0109] The present invention provides a method for preparing polylactic acid fiber, comprising the following steps:

[0110] The stereocomposite polylactic acid fiber is obtained by blending and extruding left-handed polylactic acid and right-handed polylactic acid, melt spinning, fiber annealing and fiber stretching, or by blending left-handed polylactic acid and right-handed polylactic acid at room temperature, melt spinning, fiber annealing and fiber stretching.

[0111] In the present invention, the temperature of the co-extrusion is preferably 220-240°C, more preferably 224-236°C, and more preferably 228-232°C.

[0112] In the present invention, the processing temperature of the melt spinning is preferably 220-240°C, more preferably 224-236°C, and more preferably 228-232°C.

[0113] In the present invention, the fiber annealing temperature is preferably 80 to 210°C, more preferably 110 to 180°C, and even more preferably 140 to 150°C.

[0114] In the present invention, the fiber stretching ratio is preferably 110% to 400%, more preferably 150% to 350%, and more preferably 200% to 300%.

[0115] In the present invention, the drawing temperature of the fiber drawing is preferably 80 to 210°C, more preferably 110 to 180°C, and even more preferably 140 to 150°C.

[0116] In the present invention, a block copolymer of L-lactide and D-lactide (PLLA-b-PDLA) is prepared into a stereocomposite polylactic acid fiber through the process steps of melt spinning, fiber drawing and fiber annealing.

[0117] In the present invention, the processing temperature of the melt spinning is preferably 150-240°C, more preferably 224-236°C, and more preferably 228-232°C.

[0118] In the present invention, the fiber annealing temperature is preferably 80 to 210°C, more preferably 110 to 180°C, and even more preferably 140 to 150°C.

[0119] In the present invention, the fiber stretching ratio is preferably 110% to 400%, more preferably 150% to 350%, and more preferably 200% to 300%.

[0120] In the present invention, the drawing temperature of the fiber drawing is preferably 80 to 210°C, more preferably 110 to 180°C, and even more preferably 140 to 150°C.

[0121] The present invention provides a self-reinforced absorbable composite material profile containing polyester fiber / calcium phosphate substances. The self-reinforced absorbable composite material profile containing polyester fiber / calcium phosphate substances is obtained by extruding and / or stretching a self-reinforced absorbable composite material blank containing polyester fiber / calcium phosphate substances.

[0122] The self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances includes the self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances described in any one of the above technical solutions or the self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances prepared by the preparation method described in any one of the above technical solutions.

[0123] In the present invention, the extrusion temperature is preferably 80 to 200°C, more preferably 100 to 180°C, and even more preferably 120 to 160°C.

[0124] In the present invention, the extrusion multiple is specifically that the profile length / parison length is preferably (1.2-5):1, more preferably (2-4.5):1, more preferably (2.5-4.0):1, and more preferably (3.0-3.5):1.

[0125] In the present invention, the stretching temperature is preferably 80 to 200°C, more preferably 100 to 180°C, and even more preferably 120 to 160°C.

[0126] In the present invention, the stretching multiple is specifically, profile length / parison length is preferably (1.2-5):1, more preferably (2-4.5):1, more preferably (2.5-4.0):1, more preferably (3.0-3.5):1.

[0127] In the present invention, the self-reinforced absorbable composite material profile is preferably a self-reinforced absorbable composite material profile with oriented reinforcement.

[0128] The present invention provides the use of the self-reinforced absorbable composite material described in any one of the above technical solutions, the self-reinforced absorbable composite material prepared by the preparation method described in any one of the above technical solutions, or the self-reinforced absorbable composite material profile described in any one of the above technical solutions in the preparation of implantable medical devices.

[0129] The present invention is a complete and detailed overall technical solution, which better ensures the structure and composition of the self-reinforced absorbable composite material, and further improves the mechanical properties and application performance of the self-reinforced absorbable composite material. The above-mentioned self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances and its preparation method and application can specifically include the following contents:

[0130] A self-reinforced absorbable composite material containing polyester fiber / calcium phosphate material and a preparation method and application thereof, comprising the following preparation steps:

[0131] (1) preparing a structural composite polylactic acid fiber (abbreviated as sc-PLA fiber) by mixing and extruding left-handed polylactic acid and right-handed polylactic acid, melt spinning, fiber annealing, and fiber stretching, or by mixing and extruding left-handed polylactic acid and right-handed polylactic acid at room temperature, melt spinning, fiber annealing, and fiber stretching;

[0132] The block copolymer of L-lactide and D-lactide (PLLA-b-PDLA) is prepared into a structural composite polylactic acid fiber (abbreviated as sc-PLA fiber) through the process steps of melt spinning, fiber drawing and fiber annealing;

[0133] The left-handed polylactic acid or the right-handed polylactic acid is prepared into polylactic acid fibers with high orientation and high crystallinity (hereinafter referred to as highly oriented PLA fibers) through the process steps of melt spinning, fiber stretching, and fiber annealing;

[0134] The glycolide-lactide copolymer is prepared into poly(glycolide)-lactide fiber (referred to as PLGA fiber) through the process steps of melt spinning, fiber annealing and fiber stretching;

[0135] The polyglycolide is prepared into polyglycolide fiber (PGA fiber for short) through the process steps of melt spinning, fiber annealing and fiber stretching;

[0136] Through chemical reaction, one or more of glycolide, lactide and caprolactone monomers are grafted onto the surface of calcium phosphate substances, and then ring-opening polymerization of the grafted monomers is initiated to obtain a polyester-grafted calcium phosphate substance;

[0137] (2) The polyester fiber prepared above, the grafted modified calcium phosphate substance and the absorbable polyester matrix are mixed evenly, and then the mixture is prepared into an absorbable composite material blank by injection molding or solid extrusion; or the polyester fiber prepared above, the ungrafted modified calcium phosphate substance and the absorbable polyester matrix are mixed evenly, and then the mixture is prepared into an absorbable composite material blank by injection molding or solid extrusion.

[0138] (3) The above-mentioned parison is prepared into an oriented self-reinforced absorbable composite material profile by extrusion or stretching.

[0139] (4) The above-mentioned profiles are prepared into absorbable bone screws and absorbable bone plates through mechanical processing methods such as milling, turning, and drilling.

[0140] Specifically, in the process steps for preparing sc-PLA fibers, the number average molecular weight of the left-handed polylactic acid is in the range of 50,000 to 200,000 Da, the number average molecular weight of the right-handed polylactic acid is in the range of 50,000 to 200,000 Da, and the blending mass ratio of the left-handed polylactic acid to the right-handed polylactic acid is (1:3) to (3:1); the processing temperature range of the blending extrusion is 220 to 240° C., the processing temperature range of the melt spinning is 220 to 240° C., the temperature range of the fiber annealing is 80 to 210° C., the fiber stretching multiple is 110% to 400%, and the stretching temperature range is 80 to 210° C.

[0141] Specifically, in the process steps for preparing sc-PLA fibers, the number average molecular weight of the block copolymer of L-lactide and D-lactide is in the range of 50,000 to 200,000 Da, and the molar ratio of L-lactide to D-lactide is in the range of (2:3) to (3:2); the processing temperature range of melt spinning is 150 to 240° C., the temperature range of fiber annealing is 80 to 210° C., the fiber stretching multiple is 110% to 400%, and the stretching temperature range is 80 to 210° C.

[0142] Specifically, the process steps for preparing highly oriented PLA fibers are as follows: the number average molecular weight of the L-polylactic acid or the D-polylactic acid is in the range of 50,000 to 200,000 Da, the processing temperature of the melt spinning is in the range of 150 to 200° C., the temperature of the fiber annealing is in the range of 70 to 200° C., the fiber stretching multiple is in the range of 110% to 400%, and the stretching temperature is in the range of 70 to 200° C.

[0143] Specifically, in the process steps for preparing PLGA fibers, the number average molecular weight of the glycolide-lactide copolymer is in the range of 50,000 to 200,000 Da, the molar ratio of glycolide to lactide is in the range of (1:99) to (99:1), the processing temperature of melt spinning is in the range of 150 to 250° C., the temperature of fiber annealing is in the range of 70 to 230° C., the fiber stretching multiple is in the range of 110% to 400%, and the stretching temperature is in the range of 70 to 230° C.

[0144] Specifically, in the process steps for preparing PGA fibers, the number average molecular weight of the polyglycolide is in the range of 50,000 to 200,000 Da, the processing temperature range of melt spinning is 200 to 250°C, the temperature range of fiber annealing is 70 to 230°C, the fiber stretching multiple is 110% to 400%, and the stretching temperature range is 70 to 230°C.

[0145] Specifically, the preparation method of the polyester grafted modified calcium phosphate substance, the calcium phosphate substance includes hydroxyapatite, tricalcium phosphate, and calcium phosphate substances doped with functional elements such as zinc, strontium, and magnesium; in the grafting reaction, the molar ratio of the sum of glycolide, lactide, and caprolactone monomers to the calcium phosphate substance is (1:3) to (3:1).

[0146] Specifically, in the preparation method of the absorbable composite material blank, the polyester fiber comprises one or more of sc-PLA fiber, highly oriented PLA fiber, PLGA fiber, and PGA fiber; the absorbable polyester matrix comprises one or more of left-handed polylactic acid, a copolymer of left-handed lactide and right-handed lactide, a copolymer of glycolide and lactide, and a copolymer of lactide and trimethylene carbonate (PLA-co-TMC).

[0147] Specifically, the topological structure of the left-handed polylactic acid matrix includes a linear and multi-arm (including three-arm, four-arm, six-arm, and eight-arm) structure, wherein the number average molecular weight of the linear left-handed polylactic acid matrix ranges from 80,000 to 200,000 Da, and the number average molecular weight of the multi-arm left-handed polylactic acid matrix ranges from 5,000 to 30,000 Da; the number average molecular weight of the copolymer matrix of left-handed lactide and right-handed lactide ranges from 80,000 to 200,000 Da, and the molar ratio of left-handed lactide to right-handed lactide is (85:15) to (99:1); the number average molecular weight of the copolymer matrix of glycolide and lactide ranges from 80,000 to 200,000 Da, and the molar ratio of glycolide to lactide is (1:99) to (99:1); the number average molecular weight of the copolymer matrix of lactide and trimethylene carbonate ranges from 80,000 to 200,000 Da, and the molar ratio of lactide to trimethylene carbonate is (85:15) to (99:1).

[0148] Specifically, in the absorbable composite material preform, the mass fraction of polyester fiber is 1% to 50%, the mass fraction of absorbable polyester matrix is ​​50% to 99%, and the mass fraction of calcium phosphate substances is 1% to 30%. The processing temperature range of solid extrusion is 80 to 240°C, and the processing temperature range of blending injection molding is 150 to 240°C.

[0149] Specifically, the extrusion multiple of the parison in the above step (3) is profile length / parison length, ranging from (1.2 to 5): 1, and the extrusion temperature ranges from 80 to 200°C; the stretching multiple of the parison is profile length / parison length, ranging from (1.2 to 5): 1, and the stretching temperature ranges from 80 to 200°C.

[0150] Specifically, the mechanical processing methods such as milling, turning, drilling, etc. described in step (4) can also produce absorbable bone screws with an axial hollow structure.

[0151] Furthermore,

[0152] A method for preparing a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances comprises the following steps:

[0153] (1) Preparation of sc-PLA fibers. sc-PLA fibers are prepared by using L-polylactic acid and D-polylactic acid as raw materials, in different mass ratios, through co-extrusion, melt spinning, fiber annealing, and stretching treatment; or by room temperature blending, melt spinning, fiber annealing, and fiber stretching of L-polylactic acid and D-polylactic acid; or by using block copolymers of L-lactide and D-lactide as raw materials, through melt spinning, fiber annealing, and stretching treatment to obtain sc-PLA fibers.

[0154] (2) Preparation of highly oriented PLA fibers: Using L-polylactic acid or D-polylactic acid as raw materials, highly oriented PLA fibers are prepared through melt spinning, fiber stretching, and fiber annealing.

[0155] (3) Preparation of PLGA fibers: PLGA fibers were obtained by using glycolide-lactide copolymer as raw material through melt spinning, fiber annealing and stretching.

[0156] (4) Preparation of PGA fiber: Polyglycolide is used as raw material, and polyglycolide fiber is obtained by melt spinning, fiber annealing and stretching.

[0157] (5) Preparation of polyester grafted calcium phosphate substances. One or more of glycolide, lactide, and caprolactone monomers are grafted onto the surface of calcium phosphate substances through chemical reactions, and then the grafted monomers are subjected to ring-opening polymerization to obtain polyester grafted calcium phosphate substances.

[0158] (6) Preparation of absorbable composite material preforms. The prepared polyester fiber, the grafted modified calcium phosphate substance, and the absorbable polyester matrix are used as raw materials, mixed evenly, and then processed by injection molding or solid extrusion to prepare an absorbable composite material preform; or the prepared polyester fiber, the ungrafted modified calcium phosphate substance and the absorbable polyester matrix are mixed evenly, and then processed by injection molding or solid extrusion to prepare an absorbable composite material preform.

[0159] (7) Preparation of oriented self-reinforced absorbable composite material profiles. The absorbable composite material preform is extruded by a hydraulic press to form an oriented self-reinforced profile; or stretched by a high-temperature tensile machine to form an oriented self-reinforced profile.

[0160] Specifically, the preparation steps of the sc-PLA fiber are as follows: L-polylactic acid with a number average molecular weight of 50,000 to 200,000 Da and D-polylactic acid with a number average molecular weight of 50,000 to 200,000 Da are mixed uniformly according to a mass ratio of (1:3) to (3:1), poured into a hopper of a twin-screw extruder, the temperature setting range of the extruder is 220 to 240° C., and pelletized; after drying the pellets, poured into a melt spinning machine, the processing temperature range of melt spinning is 220 to 240° C., the filament bundles are collected, and the filament bundles are selectively annealed and stretched as needed, the temperature range of the fiber annealing is 80 to 210° C., the fiber stretching multiple is 110% to 400%, and the stretching temperature range is 80 to 210° C. Or, L-polylactic acid with a number average molecular weight of 50,000 to 200,000 Da and D-polylactic acid with a number average molecular weight of 50,000 to 200,000 Da are mixed evenly in a mass ratio of (1:3) to (3:1), poured into a melt spinning machine, the processing temperature range of melt spinning is 220 to 240° C., the filament bundles are collected, and the filament bundles are selectively annealed and stretched as needed, the temperature range of fiber annealing is 80 to 210° C., the fiber stretching multiple is 110% to 400%, and the stretching temperature range is 80 to 210° C. Or a block copolymer of L-lactide and D-lactide with a number average molecular weight ranging from 50,000 to 200,000 Da is used as a raw material, poured into a melt spinning machine, the processing temperature range of melt spinning is 150 to 240° C., the filament bundle is collected, and the filament bundle is selectively annealed and stretched as needed, the fiber annealing temperature range is 80 to 210° C., the fiber stretching multiple is 110% to 400%, and the stretching temperature range is 80 to 210° C.

[0161] Specifically, the preparation steps of the highly oriented PLA fiber are as follows: pouring L-polylactic acid or D-polylactic acid with a number average molecular weight of 50,000 to 200,000 Da into a melt spinning machine, the processing temperature range of melt spinning is 150 to 200° C., the temperature range of fiber annealing is 70 to 200° C., the fiber stretching multiple is 110% to 400%, and the stretching temperature range is 70 to 200° C.

[0162] Specifically, the preparation steps of the PLGA fiber are as follows: poly(lactide) with a number average molecular weight range of 50,000 to 200,000 Da is used as a raw material, poured into a melt spinning machine, the processing temperature range of melt spinning is 150 to 250° C., the temperature range of fiber annealing is 70 to 230° C., the fiber stretching multiple is 110% to 400%, and the stretching temperature range is 70 to 230° C.

[0163] Specifically, the preparation steps of the PGA fiber are as follows: poly(lactide) with a number average molecular weight range of 50,000 to 200,000 Da is used as a raw material, poured into a melt spinning machine, the processing temperature range of melt spinning is 200 to 250°C, the temperature range of fiber annealing is 70 to 230°C, the fiber stretching multiple is 110% to 400%, and the stretching temperature range is 70 to 230°C.

[0164] Specifically, the preparation steps of the polyester graft modified calcium phosphate substance are as follows: one or more of glycolide, lactide, and caprolactone monomers, as well as hydroxyapatite and stannous octoate are poured into xylene (or toluene), heated to 100-140° C., and reacted for 1-48 hours. After cooling to room temperature, centrifugation, washing, and drying are performed to obtain the polyester graft modified calcium phosphate substance product.

[0165] Specifically, the preparation steps of the absorbable composite material blank are as follows: the prepared polyester fiber, the grafted modified calcium phosphate substance, and the absorbable polyester matrix are mixed evenly, and then the mixture is prepared into an absorbable composite material blank by injection molding or solid extrusion; or the prepared polyester fiber, the ungrafted modified calcium phosphate substance and the absorbable polyester matrix are mixed evenly, and then the mixture is prepared into an absorbable composite material blank by injection molding or solid extrusion.

[0166] Specifically, the polyester fiber comprises one or more of sc-PLA fiber, highly oriented PLA fiber, PLGA fiber, and PGA fiber; the absorbable polyester matrix comprises one or more of left-handed polylactic acid, a copolymer of left-handed lactide and right-handed lactide, a copolymer of glycolide and lactide, and a copolymer of lactide and trimethylene carbonate (PLA-co-TMC).

[0167] Among them, the topological structure of the left-handed polylactic acid matrix includes linear and multi-arm (including three-arm, four-arm, six-arm, and eight-arm) structures, wherein the number average molecular weight of the linear left-handed polylactic acid matrix ranges from 80,000 to 200,000 Da, and the number average molecular weight of the multi-arm left-handed polylactic acid matrix ranges from 5,000 to 30,000 Da; the number average molecular weight of the copolymer matrix of left-handed lactide and right-handed lactide ranges from 80,000 to 200,000 Da, and the molar ratio of left-handed lactide to right-handed lactide is (85:15) to (99:1); the number average molecular weight of the copolymer matrix of glycolide and lactide ranges from 80,000 to 200,000 Da, and the molar ratio of glycolide to lactide is (1:99) to (99:1); the number average molecular weight of the copolymer matrix of lactide and trimethylene carbonate ranges from 80,000 to 200,000 Da, and the molar ratio of lactide to trimethylene carbonate is (85:15) to (99:1).

[0168] Specifically, in the absorbable composite material blank, the mass fraction of polyester fiber is 1% to 50%, the mass fraction of absorbable polyester matrix is ​​50% to 99%, and the mass fraction of calcium phosphate substances is 1% to 30%. The processing temperature range of co-extrusion is 80 to 240°C, and the processing temperature range of co-injection molding is 150 to 240°C.

[0169] Specifically, the preparation steps of the oriented self-reinforced absorbable composite material profile are as follows: the absorbable composite material blank is extruded through a mold to be pressed into an oriented self-reinforced profile, the extrusion ratio of the blank is profile length / blank length, the range is (1.2 to 5): 1, and the extrusion temperature range is 80 to 200°C; or it is prepared into an oriented self-reinforced profile by stretching with a high-temperature tensile machine, the stretching temperature range is 80 to 200°C, and the stretching ratio of the blank is profile length / blank length, the range is (1.2 to 5): 1.

[0170] The above content of the present invention provides a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances and its preparation method and application. The polyester fiber self-reinforced absorbable composite material provided by the present invention has significantly improved mechanical properties of absorbable bone screws and absorbable bone plates, controllable degradation rate, shortened induction time of bone tissue regeneration, reduced aseptic inflammation, and stable product batches, small individual differences, and significantly improved processing efficiency. The types of polyester fibers and polyester matrices of the absorbable composite material prepared by the present invention are diverse, and the mechanical properties and degradation rate of the composite material can be regulated by matching and combining the fibers and the matrix, thereby meeting the clinical needs of fixing different fracture injuries; and the absorbable composite material prepared further adopts highly active calcium phosphate substances containing specific elements such as doped zinc, strontium, and magnesium, which can not only reduce aseptic inflammation caused by acidic degradation substances, but also have stronger osteogenic activity, angiogenesis-promoting ability, etc., thereby inducing faster healing of damaged bone tissue.

[0171] The experimental results show that the mechanical properties of the absorbable bone screws and bone plates prepared by the self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances provided by the present invention are significantly improved, among which the bending strength of the bone screw can reach 460MPa, the bending modulus can reach 8.1GPa, and the impact strength can reach 360kJ / m 2 , tensile strength can reach 210MPa, tensile modulus can reach 5.1GPa, torsional yield strength can reach 110MPa. The bending strength of the bone plate can reach 160MPa, the bending modulus can reach 4.1GPa, and the impact strength can reach 35kJ / m 2 , the tensile strength can reach 110MPa, and the tensile modulus can reach 3.1GPa.

[0172] In order to further illustrate the present invention, a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances and its preparation method and application provided by the present invention are described in detail in combination with the embodiments below. However, it should be understood that these embodiments are implemented on the premise of the technical scheme of the present invention, and detailed implementation methods and specific operating processes are given only to further illustrate the features and advantages of the present invention, rather than to limit the claims of the present invention, and the protection scope of the present invention is not limited to the following embodiments.

[0173] Example 1

[0174] Preparation of sc-PLA fiber. The synthesized L-polylactic acid with a number average molecular weight of 110,000 Da and the synthesized D-polylactic acid with a number average molecular weight of 120,000 Da were mixed evenly in a mass ratio of 1:1, poured into the hopper of a twin-screw extruder, and the temperature of each section of the extruder was 223-228°C, and pelletized; after the pellets were dried, they were poured into a melt spinning machine, and the processing temperature of each section of the melt spinning was 220-225°C, and the filaments were collected and annealed at 100°C.

[0175] Preparation of absorbable composite material preforms. The prepared sc-PLA fibers, hydroxyapatite powder, and a linear L-polylactic acid matrix with a number average molecular weight of 150,000 Da were mixed evenly, wherein the mass fraction of the sc-PLA fibers was 25%, the mass fraction of the hydroxyapatite powder was 10%, and the mass fraction of the linear L-polylactic acid was 65%; the mixture was then prepared into a composite material preform by injection molding, and the injection molding processing temperature was 200°C.

[0176] Preparation of oriented self-reinforced absorbable composite material profile: The absorbable composite material preform is extruded through a die to form an oriented self-reinforced profile, the extrusion temperature is 150°C, and the extrusion multiple of the preform is 3 times.

[0177] Forming and processing of absorbable bone screws and absorbable bone plates. The obtained profile is fixed in the clamping position of the CNC machine tool, and through the milling, turning, drilling and other mechanical processing processes of the tool, the bone screws and bone plates are made by subtractive material; the length of the bone screw is 45mm and the outer diameter is 4.5mm; the length of the bone plate is 45mm and the width is 5mm.

[0178] The bending strength of the bone screw can reach 460MPa, the bending modulus can reach 8.1GPa, and the impact strength can reach 360kJ / m 2 , tensile strength can reach 210MPa, tensile modulus can reach 5.1GPa, torsional yield strength can reach 110MPa. The bending strength of the bone plate can reach 160MPa, the bending modulus can reach 4.1GPa, and the impact strength can reach 35kJ / m 2 , the tensile strength can reach 110MPa, and the tensile modulus can reach 3.1GPa.

[0179] Comparative Example 1

[0180] Preparation of absorbable preforms: Linear L-polylactic acid with a number average molecular weight of 150,000 Da was used to prepare preforms by injection molding, and the processing temperature of the injection molding was 200°C.

[0181] Preparation of absorbable profiles. The absorbable preform is extruded through a die to form an oriented self-reinforced profile, the extrusion temperature is 150°C, and the extrusion multiple of the preform is 3 times.

[0182] Forming and processing of absorbable bone screws and absorbable bone plates. The above-mentioned profiles are fixed in the clamping position of the CNC machine tool, and through the milling, turning, drilling and other mechanical processing processes of the tool, the bone screws and bone plates are made by subtractive material; the length of the bone screw is 45mm and the outer diameter is 4.5mm; the length of the bone plate is 45mm and the width is 5mm.

[0183] The flexural strength of the bone screw is 150MPa, the flexural modulus is 2800MPa, and the impact strength is 160kJ / m 2 , tensile strength is 110MPa, tensile modulus is 2.1GPa, torsional yield strength is 50MPa. The bending strength of the bone plate is 70MPa, the bending modulus is 1500MPa, and the impact strength is 15kJ / m 2 , tensile strength is 70MPa and tensile modulus is 1.1GPa.

[0184] Example 2

[0185] Preparation of sc-PLA fibers. The synthesized L-polylactic acid with a number average molecular weight of 130,000 Da (its H NMR spectrum is as follows Figure 1 ) and the synthesized dextrorotatory polylactic acid with a number average molecular weight of 60,000 Da (its differential scanning calorimetry curve is shown in Figure 2As shown), the mixture is mixed evenly in a mass ratio of 2:1 and poured into a melt spinning machine. The processing temperature of each section of the melt spinning is 223-226°C. The filament bundle is collected (the scanning electron microscope photo of which is shown in FIG. Figure 3 The filament bundle was annealed at 170°C.

[0186] See also Figure 1 , Figure 1 The hydrogen nuclear magnetic resonance spectrum of the L-polylactic acid synthesized in Example 2 of the present invention.

[0187] See also Figure 2 , Figure 2 The differential scanning calorimetry curve of the dextrorotatory polylactic acid synthesized in Example 2 of the present invention.

[0188] See also Figure 3 , Figure 3 Scanning electron microscope photograph of sc-PLA fibers prepared in Example 2 of the present invention.

[0189] Preparation of polylactic acid grafted hydroxyapatite. Pour lactide monomer, hydroxyapatite powder and stannous octoate into xylene, heat to 120°C and react for 12 hours. After cooling to room temperature, centrifugal separation, solvent washing and purification, and vacuum drying are performed to obtain polylactic acid grafted hydroxyapatite.

[0190] Preparation of absorbable composite material preforms. The prepared sc-PLA fibers, polylactic acid grafted hydroxyapatite, and a linear L-polylactic acid matrix with a number average molecular weight of 120,000 Da were mixed evenly, wherein the mass fraction of the sc-PLA fibers was 30%, the mass fraction of the hydroxyapatite powder was 15%, and the mass fraction of the linear L-polylactic acid was 55%; the mixture was then prepared into a composite material preform by solid-state extrusion, and the processing temperature of the solid-state extrusion was 165°C.

[0191] Preparation of oriented self-reinforced absorbable composite material profiles. The absorbable composite material preform is stretched into an oriented self-reinforced profile by a high-temperature tensile machine, the stretching temperature is 160°C, and the stretching multiple of the preform is 2 times.

[0192] Forming and processing of absorbable bone screws and absorbable bone plates. The obtained profile is fixed in the clamping position of the CNC machine tool, and through the milling, turning, drilling and other mechanical processing processes of the tool, the bone screws and bone plates are made by subtractive material; the length of the bone screw is 50mm and the outer diameter is 4.0mm; the length of the bone plate is 60mm and the width is 6mm.

[0193] The bending strength of the bone screw can reach 470MPa, the bending modulus can reach 8.2GPa, and the impact strength can reach 370kJ / m 2, tensile strength can reach 230MPa, tensile modulus can reach 5.3GPa, torsional yield strength can reach 120MPa. The bending strength of the bone plate can reach 170MPa, the bending modulus can reach 4.2GPa, and the impact strength can reach 40kJ / m 2 , the tensile strength can reach 120MPa, and the tensile modulus can reach 3.3GPa.

[0194] Comparative Example 2

[0195] Preparation of absorbable preforms: Linear L-polylactic acid with a number average molecular weight of 120,000 Da was used to prepare a preform by solid extrusion, and the processing temperature of the solid extrusion was 165°C.

[0196] Preparation of absorbable profiles: The absorbable preform is stretched into an oriented self-reinforced profile by a high-temperature tensile machine, the stretching temperature is 160°C, and the stretching ratio of the preform is 2 times.

[0197] Forming and processing of absorbable bone screws and absorbable bone plates. The above-mentioned profiles are fixed in the clamping position of the CNC machine tool, and are made into bone screws and bone plates through mechanical processing methods such as milling, turning, drilling, etc.; the length of the bone screw is 50mm and the outer diameter is 4.0mm; the length of the bone plate is 60mm and the width is 6mm.

[0198] The bending strength of the bone screw is 160MPa, the bending modulus is 3.5GPa, and the impact strength is 170kJ / m 2 , tensile strength is 120MPa, tensile modulus is 2.3GPa, torsional yield strength is 60MPa. The bending strength of the bone plate is 80MPa, the bending modulus is 1.8GPa, and the impact strength is 20kJ / m 2 , tensile strength is 80MPa and tensile modulus is 1.3GPa.

[0199] Example 3

[0200] Preparation of PLGA fibers. The synthesized glycolide-lactide copolymer with a number average molecular weight of 100,000 Da and a molar ratio of glycolide to lactide of 10:90 was poured into a melt spinning machine, and the processing temperature of each section of the melt spinning was 220-225°C. The filaments were collected and stretched at a stretching multiple of 150% and a stretching temperature of 190°C.

[0201] Preparation of absorbable composite material preforms. The polyester matrix is ​​a blend of glycolide and lactide copolymer with a number average molecular weight of 100,000 Da (the molar ratio of glycolide to lactide is 50:50) and linear L-polylactic acid with a number average molecular weight of 110,000 Da, and the blending ratio is 15:85. The polyester matrix, the prepared PLGA fiber, and tricalcium phosphate doped with zinc are evenly mixed, wherein the mass fraction of PLGA fiber is 25%, the mass fraction of tricalcium phosphate doped with zinc is 15%, and the mass fraction of polyester matrix is ​​60%; the mixture is then prepared into a composite material preform by injection molding, and the injection molding temperature is 210°C.

[0202] Preparation of oriented self-reinforced absorbable composite material profile: The absorbable composite material preform is extruded through a die to form an oriented self-reinforced profile, the extrusion temperature is 155°C, and the extrusion multiple of the preform is 3.5 times.

[0203] Forming and processing of absorbable bone screws and absorbable bone plates. The obtained profile is fixed in the clamping position of the CNC machine tool, and through the milling, turning, drilling and other mechanical processing processes of the tool, the bone screws and bone plates are made by subtractive material; the length of the bone screw is 60mm and the outer diameter is 3.5mm; the length of the bone plate is 55mm and the width is 7mm.

[0204] The bending strength of the bone screw can reach 480MPa, the bending modulus can reach 8.3GPa, and the impact strength can reach 380kJ / m 2 , tensile strength can reach 240MPa, tensile modulus can reach 5.2GPa, torsional yield strength can reach 130MPa. The bending strength of the bone plate can reach 180MPa, the bending modulus can reach 4.3GPa, and the impact strength can reach 45kJ / m 2 , the tensile strength can reach 125MPa, and the tensile modulus can reach 3.5GPa.

[0205] Comparative Example 3

[0206] Preparation of absorbable preforms. The polyester matrix is ​​a blend of glycolide and lactide copolymer with a number average molecular weight of 100,000 Da (the molar ratio of glycolide to lactide is 50:50) and linear L-polylactic acid with a number average molecular weight of 110,000 Da, with a blending ratio of 15:85. The polyester matrix is ​​prepared into a composite material preform by injection molding, and the injection molding temperature is 210°C.

[0207] Preparation of absorbable profiles: The absorbable preform is extruded through a die to form an oriented self-reinforced profile, the extrusion temperature is 155°C, and the extrusion multiple of the preform is 3.5 times.

[0208] Forming and processing of absorbable bone screws and absorbable bone plates. The above-mentioned profiles are fixed in the clamping position of the CNC machine tool, and the bone screws and bone plates are made by cutting materials through machining processes such as milling, turning, and drilling. The length of the bone screw is 60mm and the outer diameter is 3.5mm; the length of the bone plate is 55mm and the width is 7mm.

[0209] The bending strength of the bone screw is 140MPa, the bending modulus is 2.3GPa, and the impact strength is 160kJ / m 2 , tensile strength is 123MPa, tensile modulus is 2.4GPa, torsional yield strength is 65MPa. The bending strength of the bone plate is 65MPa, the bending modulus is 1.9GPa, and the impact strength is 26kJ / m 2 , the tensile strength is 77MPa and the tensile modulus is 1.9GPa.

[0210] The above is a detailed introduction to a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances and its preparation method and application provided by the present invention. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method and core ideas of the present invention, including the best mode, and also enables any technician in the field to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, the present invention can also be improved and modified in several ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements that are not different from the text of the claims, or if they include equivalent structural elements that are not substantially different from the text of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A self-reinforced absorbable composite material containing polyester fiber / calcium phosphate material, characterized in that: include: An absorbable polyester material matrix and polyester fibers and calcium phosphate materials compounded in the absorbable polyester material matrix; The absorbable polyester material matrix includes one or more of a L-polylactic acid matrix, a copolymer matrix of L-lactide and D-lactide, a copolymer matrix of glycolide and lactide, and a copolymer matrix of lactide and trimethylene carbonate; The polyester fiber includes one or more of stereocomposite polylactic acid fiber, highly oriented polylactic acid fiber, poly(lactide-glycolide) fiber and poly(glycolide) fiber; The calcium phosphate material includes one or more of calcium phosphate substances, polyester grafted calcium phosphate substances, and calcium phosphate substances doped with functional elements.

2. The self-reinforced absorbable composite material according to claim 1, characterized in that: The calcium phosphate substances include hydroxyapatite and / or tricalcium phosphate; The polyester monomer in the polyester graft-modified calcium phosphate substance includes one or more of glycolide, lactide and caprolactone monomers; The functional elements include one or more of zinc, strontium and magnesium; In the self-reinforced absorbable composite material, the mass fraction of the polyester fiber is 1% to 50%; In the self-reinforced absorbable composite material, the mass fraction of the absorbable polyester material matrix is ​​50% to 99%; In the self-reinforced absorbable composite material, the mass fraction of calcium phosphate substances is 1% to 30%.

3. The self-reinforced absorbable composite material according to claim 1, characterized in that: The stretching ratio of the highly oriented polylactic acid fiber is 110% to 400%; The topological structure of the L-polylactic acid matrix includes a linear structure and a multi-arm structure; The number average molecular weight of the linear structured L-polylactic acid is 80,000 to 200,000 Da; The number average molecular weight of the multi-arm structured L-polylactic acid is 5,000 to 30,000 Da.

4. The self-reinforced absorbable composite material according to claim 1, characterized in that: The stereocomposite polylactic acid fiber is prepared from left-handed polylactic acid and right-handed polylactic acid or prepared from a block copolymer of left-handed lactide and right-handed lactide; The number average molecular weight of the L-polylactic acid is 50,000 to 200,000 Da; The number average molecular weight of the dextrorotatory polylactic acid is 50,000 to 200,000 Da; The number average molecular weight of the block copolymer of L-lactide and D-lactide is 50,000 to 200,000 Da; The self-reinforced absorbable composite material is a material for implanting medical devices.

5. A method for preparing a self-reinforced absorbable composite material containing polyester fiber / calcium phosphate material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The polyester fiber, the calcium phosphate material and the absorbable polyester material matrix are mixed by injection molding or solid extrusion to obtain a self-reinforced absorbable composite material; The stereocomposite polylactic acid fiber is obtained by co-extrusion of left-handed polylactic acid and right-handed polylactic acid, melt spinning, fiber annealing and fiber stretching; or by room temperature blending of left-handed polylactic acid and right-handed polylactic acid, melt spinning, fiber annealing and fiber stretching; or by melt spinning, fiber stretching and fiber annealing of a block copolymer of left-handed lactide and right-handed lactide; The highly oriented polylactic acid fiber is obtained by melt spinning, fiber stretching and fiber annealing of left-handed polylactic acid or right-handed polylactic acid; The poly(glycolide-lactide) fiber is obtained by melt spinning, fiber annealing and fiber stretching of glycolide-lactide copolymer; The polyglycolide fiber is obtained by melt spinning, fiber annealing and fiber stretching of polyglycolide.

6. The self-reinforced absorbable composite material according to claim 5, characterized in that: The polyester graft-modified calcium phosphate substance is obtained by grafting one or more of glycolide monomers, lactide monomers and caprolactone monomers onto the surface of calcium phosphate substances or calcium phosphate substances doped with functional elements through chemical reactions, and then initiating ring-opening polymerization of the monomers; In the chemical reaction, the molar ratio of one or more of the glycolide monomer, the lactide monomer and the caprolactone monomer to the calcium phosphate substance or the calcium phosphate substance doped with the functional element is (1:3) to (3:1); In the process of preparing stereocomposite polylactic acid fiber from L-polylactic acid and D-polylactic acid, the processing temperature of the co-extrusion is 220-240°C; the processing temperature of the melt spinning is 220-240°C; the temperature of the fiber annealing is 80-210°C; the multiple of the fiber stretching is 110%-400%; the temperature of the fiber stretching is 80-210°C; the mass ratio of the L-polylactic acid to the D-polylactic acid is (1:3)-(3:1); In the process of preparing stereocomposite polylactic acid fiber from the block copolymer of left-handed lactide and right-handed lactide, the processing temperature of the melt spinning is 150-240°C; the temperature of the fiber annealing is 80-210°C; the fiber stretching multiple is 110%-400%; the fiber stretching temperature is 80-210°C; the molar ratio of left-handed lactide to right-handed lactide in the block copolymer of left-handed lactide and right-handed lactide is (2:3)-(3:2).

7. The self-reinforced absorbable composite material according to claim 5, characterized in that: In the process of preparing highly oriented polylactic acid fiber from L-polylactic acid or D-polylactic acid, the processing temperature of melt spinning is 150-200° C.; the temperature of fiber annealing is 70-200° C.; the fiber stretching multiple is 110%-400%, and the fiber stretching temperature is 70-200° C.; the number average molecular weight of L-polylactic acid or D-polylactic acid is independently selected from 50,000 to 200,000 Da; In the process of preparing poly(glycolide-lactide) fiber from the glycolide-lactide copolymer, the processing temperature of the melt spinning is 150-250° C.; the temperature of the fiber annealing is 70-230° C.; the fiber stretching multiple is 110%-400%, and the fiber stretching temperature is 70-230° C.; the number average molecular weight of the glycolide-lactide copolymer is 50,000-200,000 Da; In the process of preparing polyglycolide from polyglycolide, the processing temperature of melt spinning is 200-250°C; the temperature of fiber annealing is 70-230°C; the fiber stretching multiple is 110%-400%, and the fiber stretching temperature is 70-230°C; the number average molecular weight of polyglycolide is 50,000-200,000 Da; The processing temperature of the solid state extrusion is 80 to 240°C; The processing temperature of the blending injection molding is 150-240°C.

8. A self-reinforced absorbable composite material profile containing polyester fiber / calcium phosphate material, characterized in that: The self-reinforced absorbable composite material profile containing polyester fiber / calcium phosphate substances is obtained by extruding and / or stretching a self-reinforced absorbable composite material blank containing polyester fiber / calcium phosphate substances; The self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances includes the self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances described in any one of claims 1 to 4 or the self-reinforced absorbable composite material containing polyester fiber / calcium phosphate substances prepared by the preparation method described in any one of claims 5 to 7.

9. The self-reinforced absorbable composite material profile according to claim 8, characterized in that: The extrusion temperature is 80-200°C; The extrusion multiple is specifically, profile length / parison length is (1.2-5):1; The stretching temperature is 80 to 200° C. The stretching multiple is specifically, profile length / parison length is (1.2-5):1; The self-reinforced absorbable composite material profile is specifically a self-reinforced absorbable composite material profile with oriented reinforcement.

10. Use of the self-reinforced absorbable composite material profile described in any one of claims 1 to 4, the self-reinforced absorbable composite material profile prepared by the preparation method described in any one of claims 5 to 7, or the self-reinforced absorbable composite material profile described in any one of claims 8 to 9 in the preparation of implantable medical devices.

Citation Information

Cited By

  • Fiber-reinforced polymer, preparation method thereof and internal fracture fixation product

    CN119930997A